2016
DOI: 10.18632/oncotarget.11793
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of CD8+TILs, PD-L1 and Foxp3+TILs in stage I NSCLC guiding adjuvant chemotherapy decisions

Abstract: PurposeCurrently, adjuvant chemotherapy is recommended for patients with high risk stage I non-small cell lung cancer (NSCLC). However, identifying high risk patients remains a challenge. This study aims to identify the patient cohorts more likely to benefit from adjuvant chemotherapy based on the tumor micro-immune environment.ResultsCD8+TILs significantly associated with disease-free survival (DFS) and overall survial (OS) (p=0.002; 0.040). Patients with high risk factors may also predict shorter DFS (P=0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 55 publications
3
37
4
Order By: Relevance
“…A study that included patients with surgically resected stage I NSCLC showed that CD8+TILs, but not PD-L1, was associated with increased disease-free survival (DFS) and OS. 13 In another study showing similar findings, a positive impact of CD8+ expression on survival of resected NSCLC patients was shown only in those with low PD-1-to-CD8 ratio. 21 A French study for patients with surgically treated basaloid squamous cell lung carcinoma (stage I-II, 68%) reported that patients with high PD-L1 expression together with increased PD-1+ and CD8+TILs were associated with an 87% reduction of death risk compared to those with low expression of all three markers.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A study that included patients with surgically resected stage I NSCLC showed that CD8+TILs, but not PD-L1, was associated with increased disease-free survival (DFS) and OS. 13 In another study showing similar findings, a positive impact of CD8+ expression on survival of resected NSCLC patients was shown only in those with low PD-1-to-CD8 ratio. 21 A French study for patients with surgically treated basaloid squamous cell lung carcinoma (stage I-II, 68%) reported that patients with high PD-L1 expression together with increased PD-1+ and CD8+TILs were associated with an 87% reduction of death risk compared to those with low expression of all three markers.…”
Section: Discussionmentioning
confidence: 67%
“…However, inconsistent findings from positive to negative or insignificant results were reported for the prognostic value of these biomarkers. 13,[21][22][23][24] In this study, we suggest additional findings for clinical impact of expression of CD8 and PD-L1 as prognostic biomarkers in NSCLC patients treated with surgical resection.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meta‐analyses revealed that CD8 + T cells have a positive effect on OS, with a HR of 0.71 (95% CI 0.62‐0.82), and are effective prognostic predictors for OS and DSS in breast cancer . CD8 + T cells were also predictors for OS and disease‐free survival (DFS) in stage I non‐small cell lung cancer …”
Section: Discussionmentioning
confidence: 99%
“…28 CD8 + T cells were also predictors for OS and disease-free survival (DFS) in stage I non-small cell lung cancer. 29 A recent meta-analysis on tumor-infiltrating immune cells suggested that the amount and density of tumor-infiltrating CD8 + T cell also affected survival in HNSCC patients, 30 whereas there is controversy as to whether higher levels of tumor-infiltrating CD8 + T cells improve survival in patients with OSCC. Several studies indicated that tumor-infiltrating immune cells did not provide any survival benefit in patients with OSCC.…”
Section: Discussionmentioning
confidence: 99%